Common Coupled Fixed-Point Theorems in Generalized Fuzzy Metric Spaces - K. P. R. Rao; I. Altun; S. Hima Bindu (Advances in Fuzzy Systems)
We prove two unique common coupled fixed-point theorems for self maps in symmetric G-fuzzy metric spaces.